OVERVIEW OF ZAKAT COLLECTION IN LAZISNU SINGGAHAN TUBAN - Irawan, Agus Wahyu; Sifa', Moh. Agus (Jurnal Ekonomi Syariah Darussalam, 2023)
The problem of povertyis still a classic problem in this country that still cannot be resolved. Poverty is increasingly coming to the fore, especially in various regions in Indonesia as a result of the economic downturn. Thus, of course, a precise and accurate formulation is needed to minimize the poverty rate. Zakat is one instrument to make it happen. The research that the researcher did was included in descriptive research with a qualitative approach. The results showed that zakat management efforts at LAZISNU Singgahan were carried out through ball pick-up services, promotions, account transfers, and establishing emotional relationships with the community.However, in the management of zakat there are obstacles that make the management of zakat at LAZISNU Singgahan not maximal in its implementation, including the human resources working at LAZISNU Singgahan where mustahiq are less active in participating in programs held by LAZISNU Singgahan and their assistance is lessthan optimal, causing a lack of understanding community towards the program run by LAZISNU Singgahan.